Hermeneutika Fakhruddin Al-Razi - Mustapa (AN NUR: Jurnal Studi Islam, 2015)
According Esack hermeneutics that it is already there in the middle of the century repertoire tafsir even classical, though not declared definitive. From that point on, this article attempts to examine medieval interpretation in this case interpretation Mafatih al-Ghaib work Fakhruddin al-Razi. To reveal the truth of the idea Esack, Is hermeneutics actually been there at that time or not? After learning hermeneutic Fakhruddin al-Razi Islamic scholarship may have wealth and finding variants that are beneficial to acknowlege Islamic scholarship